Kaj je Bela knjiga o prevajanju in zakaj jo potrebujemo? - Pregelj, Barbara (Hieronymus, 2025)
This paper presents the White Paper on Translation, a basic text on language professions and practitioners in Slovenia, which presents the state of translation, analysis, systemic and specific challenges, and examples of good practice in the field of translation, interpreting and proofreading. All Slovenian translation associations and societies, as well as all Slovenian universities, have contributed to its preparation. It contains contributions by 41 authors, divided into six thematic sections: types of translation, infrastructure of Slovenian translation, analysis of various surveys conducted among different language professions at home and abroad, overview of systemic and specific challenges, and examples of good practice. Proposals for improving the situation of translation, interpreting and proofreading are also presented.